2011
DOI: 10.3390/atmos2030303
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Ground Level Area Sources in Dairy and Cattle Feedyard Operations

Abstract: A protocol that consisted of an isolation flux chamber and a portable gas chromatograph was used to directly quantify greenhouse gas (GHG) emissions at a dairy and a feedyard operation in the Texas Panhandle. Field sampling campaigns were performed 5 consecutive days only during daylight hours from 9:00 am to 7:00 pm each day. The objective of this research was to quantify and compare GHG emission rates (ERs) from ground level area sources (GLAS) at dairy and cattle feedyard operations during the summer. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 27 publications
1
30
4
Order By: Relevance
“…During September sampling, manure was accumulated on the pen surface and fermentation likely began due to the anaerobic environment of the feedlot pen manure (fresh and accumulated manure) and bedding materials (Saggar et al, 2004). Methane emissions generally vary with manure loading rates, manure microbial activity, and fluctuations in surface temperature (Mukhtar et al, 2008;Borhan et al, 2011). Bedded pen surface temperatures were always lower than those measured from nonbedded pen surfaces, although the differences were not statistically significant (p > 0.05; Table 5).…”
Section: Background Weather Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…During September sampling, manure was accumulated on the pen surface and fermentation likely began due to the anaerobic environment of the feedlot pen manure (fresh and accumulated manure) and bedding materials (Saggar et al, 2004). Methane emissions generally vary with manure loading rates, manure microbial activity, and fluctuations in surface temperature (Mukhtar et al, 2008;Borhan et al, 2011). Bedded pen surface temperatures were always lower than those measured from nonbedded pen surfaces, although the differences were not statistically significant (p > 0.05; Table 5).…”
Section: Background Weather Informationmentioning
confidence: 99%
“…Recently, Borhan et al (2011) conducted GHG emissions measurements at ground-level area source from a dairy and cattle feedlot operation in Texas. They found that pen surfaces had significantly higher CO 2 and N 2 O emissions than the compost pile and runoff pond.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rate is more than three times higher than the Australian GHG Inventory emission estimate (1.53 kg CO 2 -e/kg liveweight.year). By contrast, Borhan (2011), using flux chambers, reported 0.13 kg CO 2 -e/ kg liveweight.year (as direct N 2 O emissions) from a Texan beef feedlot over summer. The variability between these field measurements may have been due to differences in management practices, environmental conditions and measurement techniques.…”
mentioning
confidence: 89%